2018
DOI: 10.3390/md16100377
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Natural Influenza A H1N1 Virus Neuraminidase Inhibitory Peptide Derived from Cod Skin Hydrolysates and Its Antiviral Mechanism

Abstract: In this paper, a novel natural influenza A H1N1 virus neuraminidase (NA) inhibitory peptide derived from cod skin hydrolysates was purified and its antiviral mechanism was explored. From the hydrolysates, novel efficient NA-inhibitory peptides were purified by a sequential approach utilizing an ultrafiltration membrane (5000 Da), sephadex G-15 gel column and reverse-phase high-performance liquid chromatography (RP-HPLC). The amino acid sequence of the pure peptide was determined by electrospray ionization Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Many peptides will be digested into inactive peptide fragments or free amino acids and lose activity in vivo after oral administration; however, these same peptides may have significant biological activity in vitro . For example, Li et al (2018) identified a novel H1N1 virus neuraminidase inhibitory peptide, PGEKGPSGEAGTAGPPGTPGPQGL, from cod skin hydrolysates, and this peptide was almost inactivated after simulated gastrointestinal digestion. Most bioactive peptide drugs, such as insulin, have to be administered by parenteral routes, which is inconvenient and painful ( Di, 2015 ).…”
Section: Gastrointestinal Digestion Stabilitymentioning
confidence: 99%
“…Many peptides will be digested into inactive peptide fragments or free amino acids and lose activity in vivo after oral administration; however, these same peptides may have significant biological activity in vitro . For example, Li et al (2018) identified a novel H1N1 virus neuraminidase inhibitory peptide, PGEKGPSGEAGTAGPPGTPGPQGL, from cod skin hydrolysates, and this peptide was almost inactivated after simulated gastrointestinal digestion. Most bioactive peptide drugs, such as insulin, have to be administered by parenteral routes, which is inconvenient and painful ( Di, 2015 ).…”
Section: Gastrointestinal Digestion Stabilitymentioning
confidence: 99%
“…Moreover, time-course analysis showed that it inhibited Influenza virus in the early stage of the infectious cycle. Unfortunately, it was observed that the activity of the peptide was inactivated during the simulated in vitro gastrointestinal digestion, suggesting that oral administration was not recommended [ 152 ]. Recently, Chen et al identified an octapeptide, errKPAQP (P2), from a small library of 20 peptides, designed from the binding pocket of oseltamivir in neuraminidase.…”
Section: Peptides Targeting Namentioning
confidence: 99%
“…HA proteins are used to bind to sialic acids and then genetic material penetrates into the target cell through the material transport channel, combines with the DNA and finally many progeny viruses are formed 10‐13 . NA is responsible for catalyzing the hydrolysis of glycoside bond so that the mature virus particles eventually leave the host cells and infect new epithelial cells 14‐18 . Compared with coronavirus, S protein exists in the form of homologous trimer and its monomer can be recognized by protease.…”
Section: The Discrepancy Between Coronavirus and Influenza Virusmentioning
confidence: 99%